2020
DOI: 10.1080/19420862.2020.1807721
|View full text |Cite
|
Sign up to set email alerts
|

CD40- and CD95-specific antibody single chain-Baff fusion proteins display BaffR-, TACI- and BCMA-restricted agonism

Abstract: Antibodies that target a clinically relevant group of receptors within the tumor necrosis factor receptor superfamily (TNFRSF), including CD40 and CD95 (Fas/Apo-1), also require binding to Fc gamma receptors (FcγRs) to elicit a strong agonistic activity. This FcγR dependency largely relies on the mere cellular anchoring through the antibody's Fc domain and does not involve the engagement of FcγR signaling. The aim of this study was to elicit agonistic activity from αCD40 and αCD95 antibodies in a myeloma cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…In accordance with the hypotheses that plasma membrane-associated presentation is the major factor determining agonistic activity of conventional αCD40- and α41BB antibodies, we and others recently reported anchoring-dependent agonism of αCD40- and α41BB antibody fusion proteins carrying an anchor domain specific for plasma membrane-exposed tumor marker proteins, such as CD20 12 , BCMA 13 , FAP 23 or mesothelin 24 . In this work, we exploit this mode of action to generate bifunctional αCD40- and α41BB antibody fusion proteins combining two synergistically acting activities, namely i) conditional FcγR-independent agonism and ii) PD1-PDL1 checkpoint inhibition.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In accordance with the hypotheses that plasma membrane-associated presentation is the major factor determining agonistic activity of conventional αCD40- and α41BB antibodies, we and others recently reported anchoring-dependent agonism of αCD40- and α41BB antibody fusion proteins carrying an anchor domain specific for plasma membrane-exposed tumor marker proteins, such as CD20 12 , BCMA 13 , FAP 23 or mesothelin 24 . In this work, we exploit this mode of action to generate bifunctional αCD40- and α41BB antibody fusion proteins combining two synergistically acting activities, namely i) conditional FcγR-independent agonism and ii) PD1-PDL1 checkpoint inhibition.…”
Section: Discussionsupporting
confidence: 88%
“…This suggests that it is the sheer presentation in cell-bound form that is responsible for the high agonistic activity of FcγR-bound αCD40- and α41BB antibodies. In accordance with this idea, we recently found that antibody fusion proteins harboring an anchoring domain (AD), which recognizes a cell surface-exposed anchoring target (AT), display strong AT-dependent agonism resembling those of the FcγR-bound antibodies 12 , 13 . The much higher agonistic activity of FcγR- and AT-bound antibodies and antibody fusion proteins correspond well with the fact that the natural activators of CD40 and 41BB, the ligands CD40L and 41BBL, are also much more active as membrane-bound molecules than in soluble form.…”
Section: Introductionmentioning
confidence: 68%
“…Plasma membrane binding-dependent agonism has, for example, been demonstrated by different groups for anti-TRAILR2 antibody fusion proteins with the ability to anchor to the plasma membrane with the help of a second antibody domain recognizing the cell surface antigens FAP, MCSP, and FolR1 ( Brunker et al, 2016 ; He et al, 2016 ; Shivange et al, 2018 ). Similarly, a 50- to >1,000-fold plasma membrane anchoring-dependent increase in their TNFR-stimulating potential has also been reported for various antibody fusion proteins targeting the category II TNFRs 4-1BB, CD27, CD40, CD95, Fn14, and TNFR2 ( Medler et al, 2019 ; Nelke et al, 2020 ).…”
Section: Tnf Receptor Activation Requirements: Consequences For the Dmentioning
confidence: 52%
“…In the past 10 years, extensive in vitro and in vivo studies have given comprehensive evidence that virtually every CD40-specific antibody elicits agonistic activity when bound to Fcγ receptors [ 68 , 123 , 127 , 128 ]. It is worth mentioning that the agonism of FcγR-interacting anti-CD40 antibodies is independent of FcγR downstream signaling [ 123 ] and can also be realized with FcγR-transfected non-immune cells e.g., [ 72 , 128 , 129 ]. Therefore, the sheer plasma membrane-associated mode of presentation of anti-CD40 antibody molecules appears to be sufficient to constitute the agonism of anti-CD40 antibody-FcγR complexes.…”
Section: Cd40 As Therapeutic Targetmentioning
confidence: 99%